The occurrence of the citrus flower moth, Prays citri (Lepidoptera: Yponomeutoidea: Praydidae) for the first time in Iran - Helen Alipanah; Mohammad Reza Damavandian; Maedeh Abdi; Lida Fekrat (نامه انجمن حشره‌شناسی ایران)
The citrus flower moth, Prays citri (Millière), was collected in Chubāgh village, Sari, Mazandaran Province, Iran, using ferolit water-based traps on Lemon trees at a greenhouse in the May and July of 2024. The considerable damages on Lemon flowers caused by this pest were observed at the same time. This is the first report of the genus and species from Iran, which was previously considered as an external quarantine pest in the country. A brief taxonomic characterization of the species, as well as the adult and genitalia figures of the examined specimens, are provided